The flipped classroom model on A2 EFL students’ vocabulary achievement in an ecuadorian university environment - Castro Flores, Mariuxi Iliana (2021)
Flipped classroom model has been applied in the last decades in different teaching fields with positive results providing as teachers as learners a good learning atmosphere for teaching development and learning acquisition. The efficacy of the flipped classroom model moves students from passive to active class participation, improving their vocabulary proficiency (Alnuayt, 2018). Learners feel motivated to learn on their own, promoting autonomous learning and the empowerment of their understandings (Lin & Hwang, 2018; Yang, Liu & Todd, 2019). Research recommends that the twenty-first century students enjoy learning through effective interaction that is why the flipped classroom model could be a powerful teaching tool in this century (Rivera, 2016) which entailed to the researcher to carry out this investigation with students from a public university in the Guayaquil city to enhance the vocabulary proficiency on A2 EFL learners using the flipped classroom model. Based on Bryman (2012), this quantitative research is based on an objectivist position because a problem exists in the society and is aligned to the ontological position (Cuba and Lincoln, 1994) because of the study groups were not affected by the intervention or vice versa. The existence of a problem regarding vocabulary entails an axiological position which is linked to the deductive methods and the positivist epistemological approach generating hypotheses which could be tested. This study worked with a sample class of 58 participants divided to class A (experimental group) and B (control group) who were tested through a pretest, posttest and a survey to know the students’ perceptions. Class A developed flipped activities in different platforms such as Cedia “Zoom,” Moodle, and Google Classroom for our classes and learning material and to measure students’ progress were used Microsoft and Google Forms, Kahoot, and Quizizz.